Hidroterapi Rendam Kaki Air Hangat terhadap Penurunan Tekanan Darah pada Lansia Hipertensi di Puskesmas Olak Kemang Kota Jambi - Kadri, Hasyim (3031-8572, 2024)
The problem that often occurs in hypertension sufferers is that they tend to be unstable due to lack of attention to lifestyle and irregular medication. Management of ways to prevent and treat hypertension is carried out using pharmacological and non-pharmacological treatments. Pharmacological treatment can reduce high blood pressure, but this treatment also has side effects if consumed for a long time, such as headaches, weakness, dizziness, liver dysfunction, heart palpitations and nausea. Management of hypertension or non-pharmacological treatment that is cheap and easy, can be done independently, is warm water foot soak hydrotherapy because warm water has an impact and physiological factors on the body, especially on the blood vessels, where warm water can make blood circulation smooth because warm water will encourage blood flow from the legs to the chest cavity and the blood will accumulate (gather) in the large blood vessels of the heart. This therapy has a temperature of around 38°C which can reduce blood pressure if this therapy is done regularly. Series of activities: 03 October 2023 to 05 March 2024, place at Olak Kemang Health Center, Jambi City for 30 participants. The results obtained by participants participating in activities were: Activity participants were able to understand the material properly, Activity participants were able to simulate the material correctly, Activity participants were able to answer correctly questions related to material evaluation.